Interpretation of Pathologic Margin after Endoscopic Resection of Gastrointestinal Stromal Tumor - Sang Gyun Kim (Korean Society of Gastrointestinal Endoscopy, 2016)
Interpretation of the pathologic margin of a specimen from a resected tumor is important because local recurrence can be predicted by the presence of tumor cells in the resection margin. Although a sufficient resection margin is recommended in the resection of gastrointestinal adenocarcinoma, it is not usually regarded strictly in cases of mesenchymal tumor, especially gastrointestinal stromal tumor (GIST), because the tumor is usually encapsulated or well demarcated, and not infiltrative. Therefore, margin positivity is not rare in the pathological evaluation of surgically or endoscopically resected GIST, and does not always indicate incomplete resection. Although a GIST may have a tumor-positive pathologic margin, complete resection may be achieved if no residual tumor is visible, and long-term survival can be predicted as in the cases with a negative pathologic margin.